Analytical methods in supramolecular chemistry - Schalley, Christoph A., 1968- (Weinheim : Wiley-VCH, 2012)
The second edition of'Analytical Methods in Supramolecular Chemistry' comes in two volumes and covers a broad range of modern methods and techniques now used for investigating supramolecular systems, e. g. NMR spectroscopy, mass spectrometry, extraction methods, crystallography, single molecule spectroscopy, electrochemisty, and many more. In this second edition, tutorial inserts have been introduced, making the book also suitable as supplementary reading for courses on supramolecular chemistry. All chapters have been revised and updated and four new chapters have been added--
Includes bibliographical references and index.
Keywords: Supramolecular chemistry; Instrumental analysis